(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION– Melasma is a hyper pigmentary disorder resulting in areas of pigmentation with irregular outline depending on the level of melanin deposition in skin. Skin pigmentation can be attributed to various causes different for circumscribed and diffuse hyperpigmentation. Clinical diagnosis though easy is better supported by tools such as woods lamp and dermoscope thereby helping in making the diagnosis more accurate and sometimes helping in monitoring the response after treatment. Conventionally used Wood’s lamp classified melasma into epidermal, dermal and mixed types. These types are better categorised by dermoscopy which is a new non-invasive office tool, coming with extra benefits. This study aims to demonstrate precision of dermoscopy over Wood’s lamp and encourages its use. MATERIAL AND METHODS– A cross sectional study of 100 patients diagnosed clinically as melasma was conducted over a period of seven months. Each patient was assessed by Wood’s lamp and then with dermoscope. Photographs were taken and clinically noted epidermal, dermal and mixed melasma types were confirmed according to the tool used. Results were compared and analysed. RESULTS– Out of 100 patients, Wood’s lamp classified 62, 30, 8 patients into epidermal, dermal and mixed melasma respectively while dermoscopy classified 43, 28 and 29 into the same. Comparison was done between the results of Wood’s lamp and dermoscopy and the degree of agreement was found to be substantial. (k= 0.6646, p<0.001%) CONCLUSION– Dermoscopy, has a broader usage over Wood’s lamp to determine the level of pigment. It also gives an edge to study the vascular and follicular features not visible through Wood’s lamp.